PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN MODEL PROBLEM BASED LEARNIING (PBL) DI SEKOLAH DASAR - Yona Yolanda (PAKAR Pendidikan, 2018)
This research aims to improve the 4 ℎ rade students’ integrated thematic learning process by using the problem based learning model. The design of the research was class action research using both qualitative and quantitative approaches. The subjects were the teacher and the 4 ℎ grade students. The research result shows that there are some improvement. The score of the lesson plan increased from 91.66% (excellent) in cycle I to 94.44% (excellent) in cycle II. In term of the teacher’s aspect, the score enhanced from 75% (good) in cycle I to 90% (exellent) in cycle II. Meanwhile, in term of student’s aspect, the score also increased from 70% (good) in cycle I to 87.5% (exellent) in cycle II.